Pediatric Headache Experience During the COVID-19 Pandemic. (October 2022) - DiSabella, Marc; Pierce, Emily; McCracken, Emily; Ratnaseelan, Aarane; Vilardo, Lauren; Borner, Kelsey; Langdon, Raquel; Fletcher, Angela A.
Objective: Headache disorders are exceedingly common in children and adolescents. The association between headaches, emotional stress, and disruptions in daily routines are well established. The goal of this study is to compare the experiences of patients with a preexisting diagnosis of a primary headache disorder in terms of headache frequency and severity, lifestyle techniques for headache prevention, screen use, and mood from before and after the onset of the COVID-19 pandemic. Methods: Patients evaluated by the Headache Clinic at Children's National Hospital between Summer 2020 and Winter 2021 were enrolled in a patient registry. Patients completed a questionnaire examining changes in headache characteristics and lifestyle factors since the onset of the COVID-19 pandemic. Results: A total of 107 patients completed the survey. Since the pandemic's onset, patients reported decreased physical activity (n = 59, 55%), increased frequency of chronic headaches from 40% (N = 42) to 50% (N = 54), and increased constant daily headaches from 22% (n = 24) to 36% (n = 38). Patients reported worsened anxiety (n = 58, 54%), mood (n = 50, 47%), and workload (n = 49, 46%). Sixty-one percent (n = 65) of patients reported using screens for school for more than 6 hours per day. The majority (n = 67, 63%) of patients indicated that they would prefer attending in-person school, with 14% (n = 15) responding that they preferred online school. Conclusion: Since the COVID-19 pandemic's onset, pediatric headache patients have experienced increasing headache frequency, worsening anxiety and mood, decreased physical activity, and increased screen usage. Although this study is limited by sample size and observational design, future population-based studies will further elucidate the impact of this pandemic on pediatric headache.